Enhancing graduation outcomes through challenge-based learning: A strategic proposal - Marino, Sonia Itati (Journal of Education and e-Learning Research, 2025)
This article examines the potential of Challenge-Based Learning (CBL) and Evidence-Based Software Engineering (ESBE) as a strategy for higher education, combining quality teaching with the development of professional skills. The article specifically aims to mitigate all-but-thesis syndrome in degree programmes. The methodology comprises three phases: the initial phase, development phase and the validation phase. Phase 1. An exploratory literature review was conducted to identify relevant theoretical and methodological components to support the proposal. The review highlighted the adaptation of the all-but-thesis (ABD) syndrome to undergraduate capstone projects and the use of Challenge-Based Learning (CBL) as a core theoretical framework. Additionally, the development of student-centered strategies involves adapting the ESBE method. Therefore, in the validation phase, the published data from defended degree projects at a public higher education institution were used as a case study. The findings of this study validate the proposal to integrate CBL and ESBE to address the research question. Practical implications: This proposal provides a foundation for formulating a strategy that links companies and universities through CBL. This could potentially reduce graduation delays and deliver technological solutions to relevant contexts. Furthermore, the proposal can be expanded to include additional theoretical elements and empirically extended to incorporate primary data sources for developing new indicators.